Pengaruh Ekstrak Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Terhadap Penurunan Tekanan Darah Tikus Putih Jantan (Rattus Norvegicus) Hipertensi - Mulyani, Sri (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Hypertension is an important risk factor for coronary disease. This happens both in developed or developing country. Starfruit (Averrhoa bilimbi L.) has chemical constituents that are benefi cial for health. Phytochemical screening showed that crude drugs starfruit leaves contain fl avonoids, saponins, tannins and steroids/triterpenoids. Tannin has diuretic effect. Tannin and fl avonoid also contain antioxidants that can decrease blood pressure.Objective: To determine of the eff ect of starfruit leaf extract to decrease blood pressure of hypertension white rats (Rattus norvegicus).Methods: This study was a pure experimental research design with pretest-posttest control group. The Number of samples was 21 white rats, which had previously been induced with 2.5% NaCl and prednisone dose of 1.5 mg/kg BW for 15 days. The samples were divided into 3 groups; group 1 was given captopril treatment dose of 2.5 mg/kg BW, group 2 was given a dose of starfruit leaf extract 52.517 mg/100 gram BW; and group 3 was given doses of leaf starfruit extract 105.034 mg/100 gram BW of the rats. Treatment was given for 15 days and then the blood pressure of the white rats was measured.Results: captopril dose 2.5 mg/kg BW was effective to decrease the white rats blood pressure (P 0.05). The Starfruit leaf extract dose 52. 517 mg/100 gram BW was effective to decrease white rats blood pressure (P 0.05) and starfruit leaf extract dose 105. 034 mg/100 gram BW was effective to decrease white rats blood pressure (p 0.05).Conclusion: captopril dose 2.5 mg/kg BW and starfruit leaf extract dose 105. 034 mg/100 gram BW mice had similar effectiveness to decrease white rats blood pressure.Keywords: antioxidant, blood pressure, diuretic, starfruit